2013
DOI: 10.1016/j.ridd.2013.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Mood symptoms in children and adolescents with autism spectrum disorders

Abstract: Asperger Syndrome (AS) and High Functioning Autism (HFA) are psychiatric conditions belonging to the Autistic Spectrum Disorders (ASDs), characterized by social dysfunction and focused interest, in the absence of mental retardation. Previous reports suggest that AS/HFA may be associated with important psychiatric comorbidities. Among the psychiatric internalizing disorders, depression and anxiety are probably the most common disorders. The aim of this study is to evaluate the prevalence of mood disorders and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 66 publications
0
39
0
Order By: Relevance
“…Depression is clearly also a very common problem in AS (Mazzone et al 2013;Lugnegård et al 2011) and needs to be monitored in all patients at every follow-up point. Depression in AS may be related to ongoing bullying or It is perhaps of significance that there was only one case of schizophrenic psychosis in the whole sample.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is clearly also a very common problem in AS (Mazzone et al 2013;Lugnegård et al 2011) and needs to be monitored in all patients at every follow-up point. Depression in AS may be related to ongoing bullying or It is perhaps of significance that there was only one case of schizophrenic psychosis in the whole sample.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years several efforts have been made to assess the correlation between ASD and mood disorders (Mazzone et al, 2013;Mazzone et al, 2012;Pine et al, 2008;Simonoff et al, 2013;Simonoff et al, 2012;Towbin et al, 2005).…”
Section: Mood Disorders In Asdmentioning
confidence: 99%
“…Regarding co-occurring comorbid psychopathology among samples with ASD, the majority of studies failed to identify any gender differences (Hofvander et al 2009;Lugnegard et al 2011;Matson and Nebel-Schwalm 2007;Park et al 2012;Simonoff et al 2008;Lai et al 2011;Mazzone et al 2013). However, some studies reported that girls with ASD appeared to be at greater risk than boys for internalizing psychopathology (Solomon et al 2012;Mazzone et al 2012).…”
Section: Introductionmentioning
confidence: 99%